How does social learning facilitate urban disaster resilience? A systematic review. (1st January 2020) - Zhang, Qingxia; Hu, Junyan; Song, Xuping; Li, Zhihong; Yang, Kehu; Sha, Yongzhong
ABSTRACT: Social learning has been considered an emerging policy option for urban disaster risk management. Urban disaster resilience is claimed to be a desirable outcome of many social learning programmes, but little systematic evidence illustrates how urban disaster resilience has been facilitated by social learning programmes. This paper presents a theoretic approach by a systematic review using the thematic content analysis method and finds that all of the social, technological and natural hazards can trigger social learning and the learning type varies according to 'who learns'. It is showed that the mechanisms by which social learning can facilitate urban disaster resilience include: (1) governance capacity; (2) self-organisation; (3) cognitive change; (4) moral or civic responsibility; and (5) open communication and deliberation. Moreover, the leading roles in the risk management practice played by social learning to improve urban disaster resilience are achieved throughout three strategies: (1) meeting the public demands of risk perception; (2) getting more stakeholders involved into a collaborative process; and (3) joint problem-solving. The findings might provide guidelines for the implementation of social learning programme in the future.